2021
DOI: 10.3389/fpsyg.2021.687106
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Acute and Chronic Cannabis Use on Stress Response Regulation: Challenging the Belief That Cannabis Is an Effective Method for Coping

Abstract: Although research has only recently started to examine the impact of cannabis use on stress response, there is some evidence that indicates acute and chronic impacts of cannabis on these processes. In this paper, we review processes involved in regulating the stress response and we review the influence of acute and chronic exposure to cannabis on patterns and regulation of the stress response. We also highlight the role of stress as a risk factor for initiation and maintenance of cannabis use. In this context,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 168 publications
(214 reference statements)
0
9
0
1
Order By: Relevance
“…A recent study showed that there is a bidirectional relationship between marijuana use and elevated mental stress; more specifically, stress drives the use of marijuana, and, in turn, chronic use of marijuana alters the pathways of normal stress response resulting in increased anxiety and depression 26 . Furthermore, due to the long duration and chronic nature of functional disabilities, PWD may be at greater risk of marijuana use disorder than PWoD.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that there is a bidirectional relationship between marijuana use and elevated mental stress; more specifically, stress drives the use of marijuana, and, in turn, chronic use of marijuana alters the pathways of normal stress response resulting in increased anxiety and depression 26 . Furthermore, due to the long duration and chronic nature of functional disabilities, PWD may be at greater risk of marijuana use disorder than PWoD.…”
Section: Discussionmentioning
confidence: 99%
“…Ebenso moduliert wird das endogene Verstärkersystem (Belohnungssystem). Cannabinoide beeinflussen hierüber die Verarbeitung von Stress- [1] und Schmerzreizen [54], die Bewertung von positiven [19] oder negativen [30] Stimuli, Lernprozesse [13] und sind indirekt an der Verhaltenssteuerung [38] beteiligt. Damit können auch dysfunktionale Verhaltensadaptionen und Suchtverhalten induziert werden.…”
Section: Cannabis Bei Psychischen Störungenunclassified
“…Animal studies reveal that long‐term exposure to cannabinoids during adolescence induces anxiety‐like behaviors in adulthood with concurrent serotonergic hypoactivity and noradrenergic hyperactivity 43 . Furthermore, cannabis may alter stress response both acutely and chronically, which can foster maladaptive coping and poor psychological distress tolerance 44 …”
Section: Potential Effects On Emotional and Behavioral Healthmentioning
confidence: 99%
“… 43 Furthermore, cannabis may alter stress response both acutely and chronically, which can foster maladaptive coping and poor psychological distress tolerance. 44 …”
Section: Potential Effects On Emotional and Behavioral Healthmentioning
confidence: 99%